LUNG INVOLVEMENT IN SYSTEMIC LUPUS ERYTHEMATOSUS: WELL-KNOWN FACTS AND UNSOLVED ISSUES - N. G. Klyukvina; E. A. Aseeva; N. O. Nikonorova (Научно-практическая ревматология)
The review presents the data available in the literature on the clinical manifestation, diagnostic methods,  histological features, prognosis, and response to therapy of various lung injuries in systemic lupus erythematosus (SLE). The authors give their own data on the spectrum of pulmonary diseases in patients with SLE and describe a clinical case.